Usuários de informação sobre os impactos da informatização: um estudo exploratório-metodológico - Freitas, Lidia Silva de (1989)
Exploratory and methodological study focusing the users of information on the impacts of informatics. In tge short range, it aims at: a) enlarging the existing knowledge about their diversified profiles as well as their behavior in searching and using this kind of information, and b) contributing for the refinement of both methods and techniques of data collection and analysis. In the long range its aim is to serve as a basis for a large survey among these users in order to collect the necessary data for the planning of specialized information services on the subject The study reports in detail the development, application and test of the research instruments, and the analysis of the data collected from a pilot-group, emphasizing its merits and limitations.